Міркування щодо концепцій культурогенезу - Отрощенко, В.В. (Археологія і давня історія України, 2021)
Статтю присвячено дискусії довкола осередків
культурогенезу, яка трансформувалась впродовж
останніх років у зіставлення осередково-пульсаційної та осередково-акумулятивної концепцій культурогенезу з виходом на періодизацію бронзової доби півдня Східної Європи з позицій археології чи преісторії. The concept of centers of culturogenesis, formulated
and developed by V. Bochkarev was accepted and
caused a number of considerations, clarifications and
links to the regions of Eurasia during the Paleometal
era. The implementation of the topic «Culturogenesis
in the Eneolithic — Bronze Age in Ukraine» at the Institute
of Archaeology of the National Academy of Sciences
of Ukraine brought the attention to the problems
of culturogenesis. V. Pankovskyi, comparing the points
of the participants in the discussion on the vision of the
manifestations of culturogenesis, determined the existence
of two of its concepts — center-pulsating and center-
accumulative. The researcher believes that the existing
concepts of culturogenesis are different approaches
to understanding the essence of cultural deposits,
based on the principles of archaeology or prehistory.
V. Pankovskyi’s sympathies on the side of archaeology
and the creator of the center-pulsating concept of culturogenesis
of V. Bochkarev, who proposed the periodization
of the Bronze Age, based on technological changes
in the production of non-ferrous metals. The author
considers such periodization to be no less controversial
than the previous ones, given its limited source base.
V. Pankovskyi, based on the center-pulsating concept
of cultural genesis, concludes that the periodization of
V. Otroshchenko is not archaeological, being a cultural-
chronological scheme of regional prehistory. To my
opinion, the concept, due to its delicate substance, cannot
be applied in assessing certain periodization on its
own. However, its creators are capable of it completely.
It should be reminded that any periodization of prehistory
is a scheme. The question is the following: is the
periodization of the Bronze Age made by V. Gorodtsov
an archaeology or a scheme of regional prehistory? In
general, it is too early to draw a line between archaeology
and prehistory by comparing two concepts represented
at the level of theses and individual articles.
Both concepts of culturogenesis have already entered
the segment of prehistory, without breaking with its
archaeological «umbilical cord». Primitive archaeology
and prehistory should not be too different.